Estudo da interação do ácido esteárico com plasma de radiofrequência indutivamente acoplado - Farias, Carlos Eduardo (2013)
Plasma cleaning is a promising technology in surface treatments, with the ability to reduce the amount of organic residues in a surface throught chemical and physical interactions. Despite technological interest, its use is limited because its mechanisms still are not entirely understood. Such difficulties are related to the large chemical variety of existent organic contaminants and the use of compounds instead of single molecules. This work aims to evaluate how the applied power of plasma affects its capabilities to degrade an organic molecule. To follow the physic-chemical evolution of treated samples, a chemical model was used, known as stearic acid (C18H36O2), that is a linear chain of 18 carbons with a acid function on a extremity. The experimental study was made by using an inductively coupled RF discharge at 13,56 MHz, with Ar and Ar-10%O2 gas mixtures, being the sample immerse in the discharge. Sample temperature control was made with a water cooling system and introducing steps of plasma on and off during the experiment. Mass variation rate was used as a direct characterization of degradation process. Fourier transformed Infrared Spectroscopy (FTIR) and Nuclear magnetic resonance spectroscopy (NMR) were performed to search for residual molecular modifications. In all experimental conditions was possible to attain mass reduction from the sample when exposed to plasma if the sample was kept in the solid state. The material characterization shows the possibility of attain a high etch rate, where no structural modifications are detected.